Use of the Toxicity Index in Evaluating Adverse Events in Anal Cancer Trials: Analysis of RTOG 9811 and RTOG 0529. (22nd December 2022) - Kharofa, Jordan R.; Yothers, Greg; Kachnic, Lisa A.; Ajani, Jaffer; Meyer, Joshua E.; Augspurger, Mark E.; Okawara, Gordon S.; Garg, Madhur K.; Schefter, Tracey E.; Swanson, Todd A.; Doncals, Desiree E.; Kim, Hyun; et al.
Abstract : Novel toxicity metrics that account for all adverse event (AE) grades and the frequency of may enhance toxicity reporting in clinical trials. The Toxicity Index (TI) accounts for all AE grades and frequencies for categories of interest. We evaluate the feasibility of using the TI methodology in 2 prospective anal cancer trials and to evaluate whether more conformal radiation (using Intensity Modulated Radiation Therapy) results in improved toxicity as measured by the TI. Patients enrolled on NRG/RTOG 0529 or nonconformal RT enrolled on the 5-Fluorouracil/Mitomycin arm of NRG/RTOG 9811 were compared using the TI. Patients treated on NRG/RTOG 0529 had lower median TI compared with patients treated with nonconformal RT on NRG/RTOG 9811 for combined GI/GU/Heme/Derm events (3.935 vs 3.996, P =0.014). The TI methodology is a feasible method to assess all AEs of interest and may be useful as a composite metric for future efforts aimed at treatment de-escalation or escalation